In vivo ocular biomechanical compliance in thyroid eye disease. Issue 8 (9th December 2016) - Vellara, Hans R; Hart, Richard; Gokul, Akilesh; McGhee, Charles N J; Patel, Dipika V
Abstract : Background/aims: To compare the ocular biomechanical properties in patients with thyroid eye disease (TED) and healthy participants using a non-contact Scheimpflug-based tonometer (CorVis ST). Methods: All eyes were examined by slit lamp biomicroscopy, corneal tomography and the CorVis ST (CST). Patients with TED were examined by a fellowship trained oculoplastics specialist to determine status and assess severity. The outputs from CST and additionally derived parameters, including maximum orbital deformation (MOD), were compared between healthy participants and patients with TED using Student's t-test. Furthermore, a multiple linear regression analysis was used to control for various factors known to influence ocular biomechanical responses to an air pulse. Results: This study included 20 patients with TED and compared them with a cohort of 152 healthy participants. The mean age of patients with TED was 46.7±19.0 years and the mean age of healthy participants was 35.9±13.8 years (p=0.03). There were no statistically significant differences in gender distributions between both groups (p>0.05). Several CST parameters were significantly different between groups (p<0.05). Of note, however, MOD was significantly lower in patients with TED (0.16±0.04 mm) compared with the healthy participants (0.25±0.05 mm, p<0.001). This dissimilarity remained even after controlling for the various cofactors. Receiver-operating characteristic analysis revealed an area under the curve of 0.91±0.04 (95% CI 0.84 to 0.98, p<0.001) for MOD. Conclusions: The in vivo ocular biomechanics as measured by the CST reflects a reduced orbital compliance. This method of ocular biomechanical assessment may aid in the categorisation of TED severity and assist in monitoring and/or diagnosing TED.